2010
DOI: 10.1016/j.ijpsycho.2010.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Ageing, depression, anxiety, social support and the diurnal rhythm and awakening response of salivary cortisol

Abstract: The present study compared the cortisol awakening response and diurnal rhythm in 24 young healthy students and 48 community-dwelling older adults. The associations with diurnal cortisol and depression, anxiety and social support were also examined in relation to age. Salivary cortisol was measured over the course of one day: immediately upon awakening, 30 min later, and then 3 h, 6 h, 9 h and 12 h post-awakening. Participants completed a questionnaire measuring symptoms of anxiety and depression and social sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 84 publications
2
63
2
Order By: Relevance
“…As with risk factors, protective factors have generally pertained to individual child characteristics (e.g., temperament, cognitive style, social skills, self-efficacy, and esteem) or environmental and learning experiences such as effective parenting, high family cohesion, positive parent-child relationships (Davis et al, 2000; Dick-Niederhauser and Silverman, 2004; Jakobsen et al, 2012). The presence of positive social support networks have been found to be an important protective factor against the development of emotional disorders, particularly in the face of stressful life events (Heaney et al, 2010; Grav et al, 2012; Tsai et al, 2012). Another important protective factor is a child's coping skills repertoire (Wright et al, 2010), with problem focused coping strategies being associated with greater mastery and positive psychological adjustment than avoidant or emotion focused coping skills (Dick-Niederhauser and Silverman, 2004; Klein et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As with risk factors, protective factors have generally pertained to individual child characteristics (e.g., temperament, cognitive style, social skills, self-efficacy, and esteem) or environmental and learning experiences such as effective parenting, high family cohesion, positive parent-child relationships (Davis et al, 2000; Dick-Niederhauser and Silverman, 2004; Jakobsen et al, 2012). The presence of positive social support networks have been found to be an important protective factor against the development of emotional disorders, particularly in the face of stressful life events (Heaney et al, 2010; Grav et al, 2012; Tsai et al, 2012). Another important protective factor is a child's coping skills repertoire (Wright et al, 2010), with problem focused coping strategies being associated with greater mastery and positive psychological adjustment than avoidant or emotion focused coping skills (Dick-Niederhauser and Silverman, 2004; Klein et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding associations between cortisol and depression, previous research in other patient groups has shown inconsistent results: some studies reported that depression was associated with an increased cortisol awakening response (CAR) or higher overall cortisol levels (Fries et al, 2009;Heaney et al, 2010); other studies described a blunted CAR in patients with depression (Fries et al, 2009). Regarding day-today dynamics, Adam et al (2006), for instance, showed in a sample of 156 older adults that prior-day feelings of sadness were associated with a higher cortisol awakening response.…”
Section: Discussionmentioning
confidence: 98%
“…Individuals with supportive resources showed decreased cortisol reactivity which is accompanied by diminished activity of brain regions responsible for social separation (Eisenberger NI et al 2007, Heaney JL et al 2010. It has been reported that higher social support is closely related with higher level of anti-stress hormone, oxytocin and lower level of catecholamine which is associated with cardiovascular function (Uchino BN 2006).…”
Section: Type E Personalitymentioning
confidence: 99%